Efeitos do ácido cafeico na atividade das ectoenzimas NTPDase, 5’-nucleotidase e adenosina desaminase em ratos diabéticos tipo 1 - Pelinson, Luana Paula (2015)
Diabetes mellitus (DM) is an important health problem that affects worldwide human population. Changes in the platelet morphology and function observed in diabetes have been considered an important aggravating to the vascular complications in this pathology. Platelets have relevant properties to thrombogenesis, such as the release of ADP, a molecule capable of inducing platelet aggregation. Adenosine, derived from the hydrolysis of ATP and ADP, in turn has antiagreggant properties. The control of extracellular levels these molecules and subsequent purinergic signaling induced by them is carried out by enzymes NTPDase (Nucleotide Triphosphate Diphosphohydrolase), 5'-nucleotidase and adenosine deaminase (ADA). In this context, studies have revealed that the phenolic compounds have capacity of modulate the activity of the ectoenzymes. Among these compounds, caffeic acid, found naturally in coffee and in various fruits, vegetables and herbs, such as artichoke, apple and pear has a wide spectrum of pharmacological activities, such as antiplatelet properties. Thus, the aim of this study was to evaluate the treatment effect of caffeic acid on ectoenzymes NTPDase, 5’-nucleotidase and ADA activity in platelets as well as the blood coagulation time of diabetic rats type 1. For this, male wistar rats are divided into 6 groups (n= 8-10): Control/Oil; Control/Caffeic acid 10mg/kg; Control/Caffeic acid 50mg/kg; Diabetic/Oil; Diabetic/Caffeic acid 10 mg/kg and Diabetic/Caffeic acid 50 mg/kg, treated during 30 days, via gavage. The results demonstrated a significant decrease on ADP and AMP hydrolysis, as well as on blood coagulation time, besides a significant increase on ADA activity in diabetic rats compared to control group. Treatment with caffeic acid increased ADP and AMP hydrolysis and blood coagulation time, while prevented the increase in ADA activity. With this experiment, it was possible to demonstrate that the caffeic acid was able to modulate the ectoenzymes activities and increase the blood coagulation time in type 1 diabetic rats.